Morphometric variation among six families of larval fishes in the seagrass-mangrove ecosystem of Gelang Patah, Johor, Malaysia - Ara, Roushon; Sarker, S. M. Nurul Amin Harmuj Ali; Abd. Ghaffar, Mazlan; Arshad, Aziz (Academic Journals, 2013)
Morphometnc data of six dominant families of fish larvae were examined to observe the degree of similarity among the six families. The experiment was conducted in the seagrass-mangrove ecosystems of Gelang Patah, Johor Strait, Peninsular Malaysia. Samples of fish larvae were collected by using bongo net through 30 min subsurface tow. The six dominant families (Terapontidae, Gobndae, Sillaginidae, Nemipteridae, Blenniidae and Leiognathidae) were selected for the morphometric analysis using one-way ANOVA by SPSS and PRIMER 5 software for cluster analysis. All the morphometric characters, total length, standard length, body depth, snout length, head length, eye diameter and pre anal length of the six dominant families of the order Perciformes were found to be significantly different (p<0.05). The study is formed a basis for further extensive research to be earned out on larval fishes in Malaysian waters.